Prevalence of trematodes and nematodes in donkeys marketed in the Plaza Pecuaria Iscoconga in the province of Cajamarca, Peru - Vargas Rocha, Luis Antonio (2021)
The aim of this study was to determine the prevalence of trematodes and nematodes through the presence of eggs in faeces of creole donkeys marketed in the Plaza Pecuaria Iscoconga in Cajamarca, Peru. The work was carried out between November and December 2019 with stool samples from 73 donkeys of both sexes. The samples were analysed using the Sedimentation method modified by Rojas and Torrel for the case of trematodes and the Sheather method for the case of nematodes. All samples were positive for at least one species of parasite. The prevalence found were Fasciola hepatica 28.8 ± 10.4% (21/73), paramphistomides 0%; Strongylus spp 53.4 ± 11.4% (39/73), Trichostrongylus spp 46.6 ± 11.4% (34/73), Nematodirus spp 2.7 ± 3.7% (2/73) and Parascaris spp 2.7 ± 3.7% (2/73). It is concluded that the prevalence of parasitosis was 100%; 98.6% corresponding to nematodes, 27.4% to the association of F. hepatica with nematodes and 1.4% to only F. hepatica, without finding a significant statistical association between trematodes and nematodes.